Analysis of a grid anti-islanding impedance detection system in presence of uniform distributed noise. (1st January 2014) - Fort, Ada; Mugnaini, Marco; Simoni, Enrico; Vignoli, Valerio
The incomplete knowledge of the power distribution grid status and in particular the impossibility to constantly monitor the number of subjects (feeder) able to inject current autonomously at a known time can represent a hazardous condition for the main utility provider operators' safety. Whenever an unexpected islanding condition is induced on the utility grid, every subject injecting power on the grid should stop such injection switching to a safety shut down condition. Due to the presence of multi injecting sources on the utility grid it is possible that one or more feeders do not recognise such event and continue to supply energy to a portion of the utility grid, keeping the main provider operators unaware of such condition. Such situation is the islanding condition. The present work aims, starting from a previous paper Fort et al. (2010) at assessing the robustness of an anti-islanding detection system in presence of a uniform distributed noise sources on the grid. The anti islanding detection system is based on the injection of an interharmonic component on the grid. The single phase case is considered. In this paper it is considered the optimum tradeoff between the harmonic distortion injection of a component which is required to be both meaningful from a signal to noise ratio standpoint and low enough not to affect the overall grid THD. The aim of this paper is to prove that such device will constitute a low cost, stand alone, and reliable automatic detection system for grid disconnection detection, to be supplied in conjunction with devices like the photovoltaic (PV) inverters in order to minimise their islanding non-detection zone.